Catálise por complexos metálicos: I – Complexos de Ni(II), Cu(II) e Pd(II) com bases de Schiff na oxidação de catecóis; II – Complexos de Ru(II) com ligantes tipo-pinça na desidrogenação de álcoois - Mello, Lucas dos Santos (Universidade Federal de São Carlos, 2021)
Green Chemistry is an indispensable scientific tool for sustainable development, catalysis is one of its twelve principles through which energy waste and hazardous chemicals production can be minimized. In this sense, biomimetic catalysis is a field that takes advantage of the versatility of well-defined metal complexes inspired by natural highly efficient catalysts, such as enzymes. In the design of efficient catalysts for the oxidation of organic substrates, salen-type complexes are known as mimetic models for several metalloenzymes. Their ease of synthesis, availability and versatility of stereo-electronic properties make them suitable attractive choices. On the other hand, in the search of new and more environmentally friendly sustainable energy sources, ruthenium-pincer complexes have shown promising results as catalysts in (de)hydrogenation reactions. The use of hydrogen as energy source is attractive due to its high energy density and low waste production. Nonetheless, transporting H2 is dangerous and the use of alcohols as H2 carriers with in loco hydrogen release is a highly desirable alternative. This thesis is divided in two parts in which two different catalytic processes had been studied. In the first part, there were synthetized copper(II), nickel(II) and palladium(II) salen-type complexes with ligand derived from diaminomaleonitrile and salicylaldehydes. Those complexes were characterized by physical methods in the solid state, as elemental analysis, vibrational infrared spectroscopy (IR), and single crystal X-Rays diffraction, and in solution, by molar conductivity, nuclear magnetic resonance (NMR) and electronic spectroscopy (UV-Vis). Properties were compared in terms of substituents in the aromatic rings and metal center. Moreover, the synthesized complexes were tested as catalysts in the oxidation of 3,5-di-tert-butylcatechol by O2, in a functional biomimetic application of Catechol Oxidase enzyme. In the second part, ruthenium(II)-pincer complex with PNP and PNS ligands derived from 2-(diphenylphosphane)benzaldehyde were synthesized and characterized by 1H and 31P NMR and single crystal X-Rays diffraction crystallography. Furthermore, those complexes were tested as catalysts in the dehydrogenation of alcohols (ethanol and isopropanol) in an AAD perspective.
Metal complex catalysis: I – Ni(II), Cu(II) and Pd(II) complexes with Schiff base ligands in catechol oxidation; II – Ru(II) complexes with pincer ligands in alcohol dehydrogenation reactions
Keywords: Catálise homogênea; Química de coordenação; Bases de Schiff; Ligante tipo-pinça; Homogeneous catalysis; Coordination Chemistry; Schiff bases; Pincer-type ligands; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::CAMPOS DE COORDENACAO; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::COMPOSTOS ORGANO-METALICOS; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA